Oil and civil conflict: On and off (shore) - Jørgen Juel Andersen; Frode Martin Nordvik; Andrea Tesei (Queen Mary University of London, School of Economics and Finance, 2017)
We reconsider the relationship between oil and conflict, focusing on the location of oil resources. In a panel of 132 countries over the period 1962-2009, we show that oil windfalls increase the probability of conflict in onshore-rich countries, while they decrease this probability in offshore-rich countries. We use a simple model of conflict to illustrate how these opposite effects can be explained by a fighting capacity mechanism, whereby the government can use offshore oil income to increase its fighting capacity, while onshore oil may be looted by oppositional groups to finance a rebellion. We provide empirical evidence supporting this interpretation: we find that oil windfalls i ncrease both the number and strength of active rebel groups in onshore-rich countries, while they strengthen the government in offshore-rich ones.
Keywords: O13; D74; Q34; Q35; 330; Natural resources; Conflict; Erdölvorkommen; Marktlagengewinn; Politischer Konflikt; Welt